Divided We Survive? Multi-Level Governance and Policy Uncertainty during the First Wave of Covid-19 - Marta Angelici; Paolo Berta; Joan Costa-i-Font; Gilberto Turati (Center for Economic Studies and Ifo Institute (CESifo), 2021)
We compare health system responses to the first wave of COVID-19 pandemic in Italy and Spain. In both countries, healthcare is managed at the regional level, but the central government behaved differently in the uncertainty surrounding the first wave, leaving more autonomy to regional governments in Italy than in Spain. Upon documenting national and regional health system responses, we show evidence of a significant gap in the number of infected cases, alongside regular and emergency hospital admissions, and mortality in the two countries, both at the national and at the regional level. We then discuss several potential mechanisms, such as policy stringency, the localization of the pandemic and mobility restrictions, measurement error, and especially the regional autonomy, enjoyed by Italian regions but not by Spanish regional governments amidst a state of alarm in both countries. We find that, given the strong localized effect of the pandemic, allowing more autonomy, and fostering experimentation and local solutions explains the gap between Italy and Spain in the first wave of the pandemic.
Keywords: H75; I18; 330; regional health systems; decentralization; policy stringency; health care; Covid-19; Italy; Spain